2017
DOI: 10.1159/000484629
|View full text |Cite
|
Sign up to set email alerts
|

mTOR as Regulator of Lifespan, Aging, and Cellular Senescence: A Mini-Review

Abstract: The mechanistic target of rapamycin (mTOR) network is an evolutionary conserved signaling hub that senses and integrates environmental and intracellular nutrient and growth factor signals to coordinate basic cellular and organismal responses such as cell growth, proliferation, apoptosis, and inflammation depending on the individual cell and tissue. A growing list of evidence suggests that mTOR signaling influences longevity and aging. Inhibition of the mTOR complex 1 (mTORC1) with rapamycin is currently the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
289
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(311 citation statements)
references
References 66 publications
8
289
0
14
Order By: Relevance
“…Changes in nutritional and epigenetic state are integral to aging. This can be judged by the central role of the mTOR pathway [ 9,10 ] and histone/DNA methylation [ 58,59 ] in organismal aging. αKG has emerged as master regulatory metabolite in aging biology as it is a key TCA intermediate, a cofactor for numerous transamination reactions, [ 60,61 ] a cofactor for the prolyl hydroxylase dependent hydroxylation of the transcription factor hypoxia inducible factor‐1 (HIF‐1) [ 62–64 ] and a cofactor for epigenetic enzymes, histone, and DNA demethylases.…”
Section: Application Of Metabolomics For Biomarker Discovery In Agingmentioning
confidence: 99%
“…Changes in nutritional and epigenetic state are integral to aging. This can be judged by the central role of the mTOR pathway [ 9,10 ] and histone/DNA methylation [ 58,59 ] in organismal aging. αKG has emerged as master regulatory metabolite in aging biology as it is a key TCA intermediate, a cofactor for numerous transamination reactions, [ 60,61 ] a cofactor for the prolyl hydroxylase dependent hydroxylation of the transcription factor hypoxia inducible factor‐1 (HIF‐1) [ 62–64 ] and a cofactor for epigenetic enzymes, histone, and DNA demethylases.…”
Section: Application Of Metabolomics For Biomarker Discovery In Agingmentioning
confidence: 99%
“…In that regard, the establishment of the senescent phenotype is accompanied by an increase in the activity of mTOR, which is considered as a hallmark of organismal aging . mTOR inhibition extends life span and improves age‐related pathologies in a variety of species . Interestingly, a recent report established that mTOR is activated through a PI3K/Akt/mTOR pathway during replicative senescence in vascular smooth muscle cells .…”
Section: Oxidants and Cellular Senescence Beyond Cell Cycle Arrestmentioning
confidence: 70%
“…[104][105][106] mTOR inhibition extends life span and improves age-related pathologies in a variety of species. [80,[106][107][108] Interestingly, a recent report established that mTOR is activated through a PI3K/Akt/mTOR pathway during replicative senescence in vascular smooth muscle cells. [100] Linking geroconversion to oxidants, we have shown that activation of Akt by a O 2…”
Section: Oxidants and Geroconversionmentioning
confidence: 99%
“…Spleen cell culture. To examine T-cell growth, single-cell suspensions were prepared by mincing mice a macrolide antibiotic, is known to inhibit the target of the rapamycin (TOR) signaling pathway and extend the lifespan of genetically heterogeneous mice (20,47,52,54). Rapamycin was highly effective in inhibiting T-cell activation (IC 50 = 0.16 nM) ( Figs.…”
Section: Methodsmentioning
confidence: 99%